Student Readiness Vocational High School toward Industrial Revolution 4.0 - Prabowo, Samsul Yudi; Susuila, I Wayan; Muhaji, Muhaji; Rijanto, Tri; Munoto, Munoto; Nurlaela, Lutfiyah (International Journal for Educational and Vocational Studies, 2020)
The 4.0 industrial revolution is currently underway, the Industrial Revolution 4.0 is an industry that combines automation technology with cyber-physical technology. In accordance with the objectives of the Industrial Revolution 4.0 which was coined by Professor Klaus Schwab, a German economist and founder of the World Economic Forum, that the world would be focused on increasing production by utilizing the latest technology. Technological progress is faster then humans should be able to adapt faster. The challenges and opportunities of industry 4.0 greatly impacted people's lives, one of which was the problem of unemployment. The purpose of this study was to determine the readiness of Krian 1 Vocational School Students to face the Industrial Revolution 4.0. Criteria for measuring industry readiness 4.0 A method that compares the skills possessed by vocational students and the demands of life in the 21st century that have been reviewed by several experts. The study found that: (1) improvement of the learning process in vocational schools in the context of facing the 21st century and the 4.0 revolution and (2) improving the quality of teachers related to 21st century skills demands.